Children's work and children's well‐being: Implications for policy. (12th December 2017) - Aufseeser, Dena; Bourdillon, Michael; Carothers, Richard; Lecoufle, Olivia
Abstract: This article argues for holistic consideration of children's work. Dominant discourse on "child labour" attends only to dangers of children's work, leading to policies that damage some children's chances for development. Far from being universally negative in children's lives, appropriate work contributes to their well‐being and development, and to transitions to adulthood. Children's work can convey benefits for sustenance and quality of life, provide learning to complement and support school, offer psycho‐social benefits, particularly in building self‐esteem, and help develop social relations and responsibility. These benefits are especially critical for marginalized children. Common policies of abolishing child labour based on age of employment rather than potential harm deny such benefits to younger children.